Urban Aviation: The Future Aerospace Transportation System for Intercity and Intracity Mobility - Graham Wild (Urban Science)
This review discusses the challenges of integrating emerging transportation technologies into existing urban environments, considering their impact on equity, sustainability, and urban design. The aim is to provide readers with strategic insights and policy recommendations for incorporating aerospace innovations into transportation systems. This narrative review draws on a wide range of publications, including books, journal articles, and industry reports, to examine the multifaceted aspects of urban aviation. The review explores the scales of aerospace transport, detailing the technologies enabling urban aviation, the necessary urban adaptations to support such a system, and the social and regulatory challenges of integrating urban air mobility into existing transportation networks. The research suggests that for urban air mobility to be successfully integrated into existing transportation systems, further research is needed on the social and regulatory implications, particularly regarding equitable access, sustainable practices, and community engagement.